Inside Cover: A SIM‐MOF: Three‐Dimensional Organisation of Single‐Ion Magnets with Anion‐Exchange Capabilities (Chem. Eur. J. 34/2014). Issue 34 (18th August 2014) - Baldoví, José J.; Coronado, Eugenio; Gaita‐Ariño, Alejandro; Gamer, Christoph; Giménez‐Marqués, Mónica; Mínguez Espallargas, Guillermo
<x xml:space="preserve">Abstract</x> A SIM‐MOF by chemical design A metal–organic framework (MOF) constituted by lanthanoid single‐ion magnets (SIMs) as nodes, capable of incorporating POMs into the cavities through anion exchange, is presented by E. Coronado, G. Mínguez Espallargas et al. in their Full Paper on page 10695 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>